Analisis Pengaruh Strategi Pemasaran pada Aplikasi Tiktok Terhadap Keputusan Belanja Online Generasi Z Wilayah Jabodetabek: Price, Content Marketing, Viral Marketing dan Live Streaming Shopping - Muhammad Rezki Atthani; Achmad Syamsul Huda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
TikTok has evolved not only as a platform for entertainment and information but also as a marketing medium with great potential to reach a wide audience. This study aims to analyze the influence of price, content marketing, viral marketing, and live streaming shopping on the online purchasing decisions of Generation Z in the Jabodetabek area through the TikTok application. The research method used is a descriptive quantitative approach. The sampling technique employed is non-probability sampling, specifically purposive sampling. Using Hair's formula, a total of 210 respondents were obtained as the sample. Data was collected through the distribution of questionnaires using a 1–5 Likert scale to Generation Z individuals residing in Jabodetabek who are TikTok users and have previously made purchases through the platform. Data analysis was conducted using SEM-PLS, processed with SmartPLS 4 software. The results of the study indicate that the variables of price, content marketing, viral marketing, and live streaming shopping have a positive and significant influence on the online purchasing decisions of Generation Z in the Jabodetabek area through the TikTok application.